Pengaruh Pendapatan Asli Daerah dan Belanja Modal Terhadap Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat di Provinsi Sumatera Utara - Sarah Enjelita Simamora; Dewi Purnama Sari Br Marbun; Fatin Hanifah Zahra; Asnidar Asnidar; Ahmad Ridha (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study aims to analyze the effect of Regional Original Income (PAD) and capital expenditure on economic growth and community welfare in North Sumatra Province from 2009 to 2023. Economic growth is considered an essential indicator in assessing regional productivity, while community welfare is measured using the Human Development Index (HDI), which includes health, education, and purchasing power. This research utilizes secondary data from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance. Path analysis examines the direct and indirect effects of PAD and capital expenditure on economic growth and community welfare. The result shows that PAD has a significant positive effect on economic growth and community welfare. Conversely, capital expenditure shows a negative but insignificant effect on economic growth and a positive but insignificant effect on community welfare. This study recommends optimizing capital expenditure and improving PAD management to support more sustainable development.